Gambaran pengetahuan dokter gigi di jakarta barat Tentang rugae palatina - Annisa Aulia Ananda; Rizki Tanjung; Vanessa Utama (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: A dentist is able to be requested for help investigating a crime handled by the authorities. Hence, the knowledge of forensic odontology has to be possessed by not only forensic dentists but also all practicing dentists require having the knowledge. Dental identification is the most general method used in forensic odontology, not only tooth; palatine rugae are evidently able to be used as an alternative in personal identification method. Palatine rugae have been proven and considered to be relevant since their uniqueness in each rugae pattern. Palatine rugae have been equated with finger prints. Purpose: To obtain the illustration of the dentists’ knowledge level regarding palatine rugae in West Jakarta. Method: Descriptive observational study with cross sectional design conducted through online. The data collected from 100 respondents, all are dentists who practice in West Jakarta. A questionnaire used to measure the dentists’ knowledge. It consists of 11 closed-ended questions; score 2 given for correct answer, score 1 given for incorrect answer, and score 0 given for ‘don’t know’ answer. Result: The result of data calculation from respondents’ answers was divided into three knowledge categories. Based on the research data calculation, 36 respondents (36.0%) have good knowledge (76%-100%); 34 respondents (34.0%) have adequate knowledge (56%-75.9%); and 30 respondents (30.0%) have lack knowledge (less than 56%). Conclusion: The study obtained 36.0 % respondents have good knowledge, 34.0% respondents have adequate knowledge, and 30.0% respondents have lack knowledge.